0711 Do postmenopausal women with insomnia and obstructive sleep apnea have deterioration in sexual function?. (25th May 2022) - Ishikura, Isabela; Lucena, Leandro; Andersen, Monica; Tufik, Sergio; Girão, Manoel; Hachul, Helena
Abstract: Introduction: Sleep problems and sexual dissatisfaction are among the most common complaints during and after the menopause transition. The prevalence of insomnia and obstructive sleep apnea (OSA) reach 31% and 44% of postmenopausal women, respectively. The sexual dissatisfaction is frequently caused by a decline in hormonal levels and urogenital atrophy, resulting in inadequate lubrication and pain during intercourse, with orgasm difficulties and low sexual. Both behaviors – sleep and sexual function - play an important part in women's wellness. The objective of this study was to investigate whether insomnia in association with OSA would increase climacteric and sexual symptoms compared with women with only insomnia or OSA. Methods: Our sample comprised 47 postmenopausal women distributed into 3 groups: 1) insomnia, 2) OSA, and 3) OSA+insomnia. All participants completed the questionnaires: Insomnia Severity Index, Female Sexual Function Index, and Blatt-Kupperman menopausal index. Of the 47 participants, 34 women undergone polysomnography. The 3 groups were compared in respect of climacteric symptoms, sexual function score, and sleep. Results: Our results showed that 85.1% of the postmenopausal women were classified with insomnia, 46.8% were diagnosed with OSA, and 82.9% had low sexual function. All groups had sleep efficiency of <80%, wake after sleep onset of >65 min, and a total sleep time of <6h, indicating poor sleep quality. There were no statistically significant differences among the groups in all sexual domains. The group of OSA+insomnia reported more climacteric symptoms (27.1±9.7) when compared to OSA group (15.7±9.6, P=0.03). Conclusion: In our sample, the presence of insomnia and OSA associated with postmenopause revealed a low score for sexual function. Climacteric symptoms were higher in the groups with insomnia, and the association with low sexual function can lead to worsening of clinical condition. Support (If Any): Support: AFIP and CNPq. ACKNOWLEDGEMENTSOur studies are supported by the following funding agencies: AFIP (Associação Fundo de Incentivo à Pesquisa), CNPq (fellowships to LL, MLA, HH and ST). This study received indirect funding from AFIP and CNPq.